2001
DOI: 10.1248/cpb.49.361
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship (SAR) Studies on Oxazolidinone Antibacterial Agents. 3. Synthesis and Evaluation of 5-Thiocarbamate Oxazolidinones.

Abstract: A series of 5-thiocarbamate oxazolidinones was prepared and tested for in vitro and in vivo antibacterial activities. The results of in vitro antibacterial activity indicated that the 5-thiocarbamate group was a suitable substituent for the activity by the 5-moderate hydrophilicity. The compounds within a favorable log P value range were found to have potent in vitro antibacterial activity against gram-positive bacteria including methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…It was clear from the study that the mono halo substitution on ring D showed comparatively potent activity than the others. (9) and p-dichloro (10) substitution of D ring showed moderate activity against gram-positive organisms and exhibited poor activity against gram-negative organisms.…”
Section: Synthesis and Evaluation Of Urea And Thiourea Derivatives Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…It was clear from the study that the mono halo substitution on ring D showed comparatively potent activity than the others. (9) and p-dichloro (10) substitution of D ring showed moderate activity against gram-positive organisms and exhibited poor activity against gram-negative organisms.…”
Section: Synthesis and Evaluation Of Urea And Thiourea Derivatives Ofmentioning
confidence: 99%
“…1) potent in vitro and in vivo antibacterial agents. [6][7][8][9] In 1987, DUP 721 was selected as an antibacterial new candidate for clinical trials. However, its further development was discontinued due to toxicity observed in phase-I clinical trials.…”
mentioning
confidence: 99%
“…As replacement of 5‐acetyl group with different functionalized groups, such as chlorine or a thiocarbonyl group maintained or even increased activities against Sta. aureus (25–27), the effect of substituted acetyl groups at the 5‐position such as chloroacetyl ( 13e ), dichloroacetyl ( 13f ) and trifluoroacetyl ( 13g ) was investigated. Interestingly, 13e–g showed similar activities against Sta.…”
Section: Physical Properties Of Oxazolidinones Prepared Accordingf Tmentioning
confidence: 99%
“…The target compounds were synthesized from 3a and 3b via similar routes to those reported for the original compounds, respectively. 22,25) The new compounds 10a 26) and 10b 27) showed excellent in vitro antibacterial activity against MRSA or line- …”
mentioning
confidence: 98%
“…The target compounds were synthesized from 3a and 3b via similar routes to those reported for the original compounds, respectively. 22,25) The new compounds 10a 26) and 10b 27) showed excellent in vitro antibacterial activity against MRSA or line- 28) in comparison with linezolid (Table 1). Furthermore, compound 10a exhibited good in vivo efficacy when administered intravenously in a murine model of systemic infection, with MRSA SR3637 as the infectious organism.…”
mentioning
confidence: 99%